A20 haploinsufficiency in a neonate caused by a large deletion on chromosome 6q - Fan Zhang; Liang Zhang (BMC, 2024)
Abstract Haploinsufficiency of A20 (HA20) is a rare monogenic disease caused by heterozygous loss-of-function mutations in the tumor necrosis factor alpha-induced protein 3 (TNFAIP3) gene located on chromosome 6q23.3. The majority of disease-causing mutations in most cases of HA20 comprise single nucleotide variations, small insertions, or deletions in TNFAIP3, which result in a premature termination codon and subsequent disruption of its anti-inflammatory role. Large deletions have been reported sporadically. HA20 patients may present with a variety of autoinflammatory and autoimmune features during early childhood; however, cases with neonatal onset are rare. Here, we describe a Chinese neonate presenting with concomitant inflammatory and other syndromic manifestations caused by a 5.15 Mb interstitial deletion in chromosome 6; these deletions affect TNFAIP3. Taken together, the data extend the clinical and genetic spectra of HA20.